1979
DOI: 10.1161/01.str.10.3.335
|View full text |Cite
|
Sign up to set email alerts
|

Flow disturbances at the apex and lateral angles of a variety of bifurcation models and their role in development and manifestations of arterial disease.

Abstract: Dye flow patterns were studied in 12 glass model bifurcations with angles of 45, 90, 135, and 180 degrees, and area ratios of 0.78, 1.03 and 1.27. At the apex, the dye formed a saddle zone, and streamlines from the core which entered this region were swept over the upper and lower surfaces to enter the lateral angles. Qualitatively, the shape and size of the apex played a key role in this effect. Boundary layer separation occurred in the lateral angles, and increased as flow into the branch was reduced. If the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Malcolm and Roach [7] in an experimental investigation, evaluated the significance of the angle of division of a vessel in altering haemodynamics with its effect on the development of atherosclerotic lesions in its branches. They showed that shear stress was substantially reduced on the lateral wall of daughter branches with an increase in atherogenesis by asymmetry or irregularity of the division; imbalances of the relative flows down the daughter branches and an increased angle of division.…”
Section: Angle Of Division Of Left Main Coronary Arterymentioning
confidence: 99%
“…Malcolm and Roach [7] in an experimental investigation, evaluated the significance of the angle of division of a vessel in altering haemodynamics with its effect on the development of atherosclerotic lesions in its branches. They showed that shear stress was substantially reduced on the lateral wall of daughter branches with an increase in atherogenesis by asymmetry or irregularity of the division; imbalances of the relative flows down the daughter branches and an increased angle of division.…”
Section: Angle Of Division Of Left Main Coronary Arterymentioning
confidence: 99%
“…Recent model studies in our lab [Houle and Roach, 1981;Malcolm and Roach, 1979] suggest that both the area ratio and the curva ture of the bifurcation probably play a role in determining how the flow divides at the apex of a bifurcation. In spite of the obvious im portance of bifurcation geometry there has been no detailed analysis of the precise shape of the apical or branching region where the trunk divides into two or more branches.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have studied the various fluid dynamic effects of branching because of their presumed importance to atherogenesis. 8 " 14 On the other hand, neither flow-divider offset nor angular asymmetry have received similar attention. The purpose of this paper is to call attention to the variability in these other parmeters and to present their distributions and those of branch angle among human aortic bifurcations.…”
mentioning
confidence: 99%